PENGEMBANGAN E-MODUL BERBASIS HIGHER ORDER THINGKING SKILLS (HOTS) BERBANTUAN APLIKASI SIGIL PADA SISWA KELAS VIII SMP - Novi Hartika; Lucy Asri Purwasi; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to produce an e-module based on Higher Order Thinking Skill (HOTS) which is designed with sigil application on the material area and volume of class VIII flat surface shapes that are valid, practical and have potential effects. This research is a development research using a 4-D model. This model consists of four stages, namely: the defining stage, the design stage, the develop stage, and the dissemination stage. The subjects of this study were eighth grade students of SMP Negeri 11 Rejang Lebong, totaling 6 students for the small group and 28 students for the field test. Data collection techniques through interviews, observations, questionnaires and tests. Based on the results of data analysis carried out, the average results of HOTS-based e-module users assisted by sigil applications from the aspect of language validity, the aikien'v value of 0.89 with very valid criteria, material validity 0.65 with valid criteria, and media validity 0 ,62 with valid criteria. In the practical aspect, the practicality results obtained through the teacher's response of 88% with very practical criteria, and student responses showing a percentage of 85.4% with very practical criteria. Furthermore, in the classical aspect of completeness it reaches a percentage of 82% with very good criteria so that among 28 students only 5 students have not achieved the completeness set by the school. So it can be concluded that the implementation of HOTS-based e-modules assisted by sigil can have a potential effect and facilitate students' higher order thinking skills.